Results 1 to 4 of 4

- Oct 13th 2010, 11:41 PM #1

- Joined
- Dec 2008
- Posts
- 68

- Oct 14th 2010, 12:05 AM #2

- Oct 14th 2010, 03:51 AM #3

- Joined
- Apr 2005
- Posts
- 18,282
- Thanks
- 2456

Another way to do this: Look at the

**equation**|3x- 1|= |-x+ 4|. Since the two absolute values are the same, either the numbers themselves are the same, 3x- 1= -x+ 4, or the differ only in sigh, 3x-1= -(-x+ 4)= x- 4.

The first equation, 3x- 1= -x+ 4 gives 4x= 5 or x= 5/4. The secon gives 2x= -3 or x= -3/2.

The point is that those two points are the only points at which "<" can change to ">" and vice versa.

The number -2 is less that -3/2 and putting x= -2 in the original equation, |3(-2)-1|= |-7|= 7> |-(-2)+4)|= |6|= 6 so |3x-1|> |-x+ 4| for**all**x< -3/2.

The number 0 is**between**-3/2 and 5/4. Putting x= 0 in the original equation, |3(0)-1|= |-1|= 1< |-(0)+ 4|= |4|= 4 so |3x-1|< |-x+ 4| for**all**x between -3/3 and 5/4.

The number 2 is greater than 5/4. Putting x= 2 in the original equation, |3(2)- 1|= |5|= 5> |-(2)+ 4|= |2|= 2 so |3x-1|> |-x+ 4| for**all**x greater than 5/4.

- Oct 14th 2010, 07:13 AM #4